2020
DOI: 10.1016/j.esxm.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictive Factors of Female Sexual Dysfunction in a Sample of Saudi Women

Abstract: Introduction: Female sexual dysfunction (FSD) is a common health problem that is inadequately investigated in Saudi Arabia. Aim: To assess the prevalence and predictors of FSD in a sample of Saudi women attending the primary care and gynecology clinics. Methods: A cross-sectional clinic-based survey involved Saudi women attending primary care and gynecology clinics in a teaching hospital in Riyadh during the period from January to June 2019. Data were collected using a structured interview questionnaire. Femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 33 publications
3
31
1
3
Order By: Relevance
“…More than 40 years of age increased the risk of FSD by about five times. Many potential risk factors for FSD were suggested, including age, economic level, and satisfaction with a spouse's sexual ability were the only predictive factors [6,12] . Conversely to our results, Maaita et al reported desire problems in the majority [49.4%] of his participants, arousal problems in 31.9% and lubrication problems in 39.2%, orgasm problems in 39.57%, satisfaction problems in 43.82%, and pain problems during sexual relations in a minor proportion [19.2%] [12] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 40 years of age increased the risk of FSD by about five times. Many potential risk factors for FSD were suggested, including age, economic level, and satisfaction with a spouse's sexual ability were the only predictive factors [6,12] . Conversely to our results, Maaita et al reported desire problems in the majority [49.4%] of his participants, arousal problems in 31.9% and lubrication problems in 39.2%, orgasm problems in 39.57%, satisfaction problems in 43.82%, and pain problems during sexual relations in a minor proportion [19.2%] [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the risk of FSD may improve with the therapy of male sexual dysfunction. In Saudi Arabia, dissatisfaction with a spouse's sexual ability elevated the chance of FSD by almost six times [6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female sexual dysfunction (FSD) is a common and uncomfortable condition that affects many women worldwide [ 4 ]. The prevalence of FSD and the factors contributing to its development vary across countries and regions [ 5 ]. According to most epidemiological studies, the prevalence of FSD ranges from 37 to 40% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women's sexual problems are highly prevalent (1)(2)(3)(4)(5), with incidence estimates over 39% of women reporting sexual problems (2,6). In addition, female sexual dysfunction has a wellknown negative impact on quality of life (1), well-being (7), psychological adjustment (8,9), sexual health (10), sexual satisfaction (11)(12)(13)(14), and dyadic adjustment (15).…”
Section: Introductionmentioning
confidence: 99%